Peningkatan Kompetensi Berkomunikasi Ilmiah Dengan Laboratorium Berbantuan Komputer - Rahayu, Ratna Dwi (SIMETRIS, 2024)
In learning physics, one of the competencies that must be mastered in the competence of scientific work is the competence of scientific communication. Scientific communication can be done orally or in writing. The purpose of this research is to describe the science process skills that can be developed in guided inquiry-oriented laboratory activities and develop inquiry-oriented devices in the form of student laboratory activity sheets that can encourage student competence in scientific communication. The achievement of scientific communication competence is done by doing hands on laboratory activities and multimedia laboratories with guided inquiry insights by developing student laboratory activity sheet devices. The research method used is research and development (R&D) method. To measure the achievement of indicators used tools in the form of: evaluation (pre-test and post-test), laboratory activity sheets, laboratory activity reports, practicum observation sheets and discussions. The results of this study indicate an increase in the scientific communication competence of students who have conducted hands-on laboratory activities, especially multimedia laboratories. The conclusion that can be drawn from this research is that the inquiry-oriented student laboratory activity sheet by utilizing hands on laboratories and multimedia laboratories can be used to improve students' scientific communication skills.